Implementasi Manajemen Perubahan dalam Budaya Sekolah di RA TK Sunan Kalijaga Malang - Rahmat Adil Indra Yanuar; Iin Fatihah Tarim; Hikmawati; Mochammad Bagas Satria; Shobihatul Fitroh Noviyanti (Al-Kindi, 2026)
This study aims to examine the implementation of change management within the school culture at TK RA Sunan Kalijaga. The school culture is implemented as an effort to shape students’ character from an early age through various positive habit-forming activities. Change management is implemented to create a school environment that is religious, disciplined, clean, and conducive to learning. The application of school culture is realized through activities such as the Dhuha prayer, group Quran recitation, daily prayers, voluntary Friday donations, “Clean Friday,” and handwashing habits. The principal and teachers serve as drivers and role models in the implementation of school culture, while parents support the habits practiced at home. In its implementation, there are several challenges, such as differences in students’ personalities, a lack of support from some parents, and limited facilities and infrastructure. To address these issues, the school conducts regular communication, outreach, and program evaluations. The results of the implementation show that the school culture has a positive impact on students’ character development, such as increased discipline, religious attitudes, social awareness, and habits of clean and healthy living.